Pericytic mimicry in well-differentiated liposarcoma / atypical lipomatous tumor - Shen, Jia (Hum Pathol, 2016)
Pericytes are modified smooth muscle cells that closely enwrap small blood vessels, regulating and supporting the microvasculature through direct endothelial contact. Pericytes demonstrate a distinct immunohistochemical profile, including expression of αSMA (Smooth Muscle Actin), CD146, PDGFRβ (Platelet Derived Growth Factor Receptor β), and RGS5 (regulator of G-protein signaling 5). Previously, pericyte related antigens have been observed to be present among a group of soft tissue tumors with a perivascular growth pattern, including glomus tumor, myopericytoma and angioleiomyoma. Similarly, malignant tumor cells have been shown to pericyte-like immunoprofile when present in a perivascular location, seen in malignant melanoma, glioblastoma, and adenocarcinoma. Here, we examine well-differentiated liposarcoma specimens, which showed some element of perivascular areas with the appearance of smooth muscle (N=7 tumors). Immunohistochemical staining was performed for pericyte antigens, including αSMA, CD146, PDGFRβ, and RGS5. Results showed consistent pericytic marker expression among liposarcoma tumor cells within a perivascular distribution. MDM2 immunohistochemistry and fluorescence in situ hybridization for MDM2 revealed that these perivascular cells were of tumor origin (7/7 tumors), while double immunohistochemical detection for CD31/CD146 ruled out an endothelial cell contribution. These findings further support the concept of pericytic mimicry, already established in diverse malignancies, and its presence in well-differentiated liposarcoma. The extent to which pericytic mimicry has prognostic significance in liposarcoma is as yet unknown.